Comparative Pathobiology of Canine and Human Prostate Cancer: State of the Art and Future Directions - Nascente, Eduardo de Paula; Amorim, Renée Laufer [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP]; de Moura, Veridiana Maria Brianezi Dignani (MDPI, 2022)
First described in 1817, prostate cancer is considered a complex neoplastic entity, and one of the main causes of death in men in the western world. In dogs, prostatic carcinoma (PC) exhibits undifferentiated morphology with different phenotypes, is hormonally independent of aggressive character, and has high rates of metastasis to different organs. Although in humans, the risk factors for tumor development are known, in dogs, this scenario is still unclear, especially regarding castration. Therefore, with the advent of molecular biology, studies were and are carried out with the aim of identifying the main molecular mechanisms and signaling pathways involved in the carcinogenesis and progression of canine PC, aiming to identify potential biomarkers for diagnosis, prognosis, and targeted treatment. However, there are extensive gaps to be filled, especially when considering the dog as experimental model for the study of this neoplasm in humans. Thus, due to the complexity of the subject, the objective of this review is to present the main pathobiological aspects of canine PC from a comparative point of view to the same neoplasm in the human species, addressing the historical context and current understanding in the scientific field.
Keywords: Immunobiology; molecular biology; oncogenes; prostate carcinoma; tumor suppression